“Charanga Cakewalk”: Tejano Music Takes Center Stage - Chastagner, Claude (Complutense Journal of English Studies, 2015)
This paper explores the sounds of the Tejano community, and probe to what extent the musical production of a given ethnic group is constitutive of a global American sound, or if on the contrary, it serves to foster the interests and the leverage of the said group, unraveling in the process the very notion of a unified American culture. The study is based on the work of Michael Ramos, founder and leader of the influential band Charanga Cakewalk, a Tejano musician with typically strong roots both in the Mexican and in the US communities. The music of Charanga Cakewalk, which draws equally from the Latino and Anglo idioms, while mixing old school genres with contemporary experimentations, helps to assess the impact of staging subversive sounds that dislocate the dominant ones.